An autologous endothelial cell:peripheral blood mononuclear cell assay that detects cytokine storm responses to biologics. Issue 6 (6th March 2015) - Reed, Daniel M.; Paschalaki, Koralia E.; Starke, Richard D.; Mohamed, Nura A.; Sharp, Giles; Fox, Bernard; Eastwood, David; Bristow, Adrian; Ball, Christina; Vessillier, Sandrine; Hansel, Trevor T.; Thorpe, Susan J.; et al.
ABSTRACT: There is an urgent unmet need for human tissue bioassays to predict cytokine storm responses to biologics. Current bioassays that detect cytokine storm responses in vitro rely on endothelial cells, usually from umbilical veins or cell lines, cocultured with freshly isolated peripheral blood mononuclear cells (PBMCs) from healthy adult volunteers. These assays therefore comprise cells from 2 separate donors and carry the disadvantage of mismatched tissues and lack the advantage of personalized medicine. Current assays also do not fully delineate mild (such as Campath) and severe (such as TGN1412) cytokine storm‐inducing drugs. Here, we report a novel bioassay where endothelial cells grown from stem cells in the peripheral blood (blood outgrowth endothelial cells) and PBMCs from the same donor can be used to create an autologous coculture bioassay that responds by releasing a plethora of cytokines to authentic TGN1412 but only modestly to Campath and not to control antibodies such as Herceptin, Avastin, and Arzerra. This assay performed better than the traditional mixed donor assay in terms of cytokine release to TGN1412 and, thus, we suggest provides significant advancement and a definitive system by which biologics can be tested and paves the way for personalized medicine.—Reed, D. M., Paschalaki, K. E., Starke, R. D., Mohamed, N. A., Sharp, G., Fox, B., Eastwood, D., Bristow, A., Ball, C., Vessillier, S., Hansel, T. T., Thorpe, S. J., Randi, A. M., Stebbings, R., Mitchell, J. A. An autologous endothelial cell:peripheral blood mononuclear cell assay that detects cytokine storm responses to biologics. FASEB J. 29, 2595‐2602 (2015). www.fasebj.org